EFEKTIVITAS PEMBERIAN TERAPI MUROTTAL AL-QUR’AN UNTUK MENGONTROL NYERI PADA PASIEN FRAKTUR TERTUTUP DI IGD RS IBNU SINA YW UMI - Muhammad Irwansyah; Safruddin; Rahmat Hidayat; Fitria (Jurnal Kesehatan, 2026)
Hand fractures cause significant pain that can interfere with patients' quality of life. Effective pain management is essential for optimal recovery. Al-Qur'an recitation therapy has been proven to have a calming effect and reduce pain. This case study aims to determine the effect of Al-Qur'an recitation therapy on pain control in patients with hand fractures. This case study is a case study or learning strategy to analyse the effectiveness of Al-Qur'an recitation therapy in controlling pain in patients with distal humerus dextra fractures by providing Al-Qur'an recitation therapy. Clients focused their minds on reciting verses from Ar-Rahman for approximately 20 minutes, after which they were instructed to open their eyes. The results showed that there was a decrease in pain intensity from a previous scale of 7 to 4 after being given murottal therapy. Al-Qur'an murottal therapy is effective in controlling pain in patients with mild to moderate fractures. This therapy can be a useful non-pharmacological modality to reduce pain and improve patient welfare.